Professional Responsibility An Open-Source Casebook - Frye, Brian L.; Schiller, Elizabeth (Open textbook library., 2019)
We wanted this casebook to be as easy to use and understand as possible. Accordingly, we included not only cases, but also the text of the rules and restatements, as well as concise explanations of the relevant law. Each chapter of the book addresses a different issue, in the following format. First, it clearly and concisely explains the relevant law governing that issue. Then provides the relevant text of any statutes, Model Rules, sections of the Restatement of the Law Governing Lawyers, or other sources, with a link to an open-source versions of the full text, when available. It provides one or more heavily edited cases intended to illustrate the application of the law at issue, with a link to an open-source version of the full text of the case. Each case is preceded by a brief summary of its facts, reasoning, and holding, and followed by questions intended to indicate subjects for further investigation or discussion. And finally, it includes citations to law review articles and other materials relevant to the law at issue, with links to open-source versions of those materials, when available. This casebook covers a wide range of different subjects related to the professional responsibility of attorneys. While it is possible to cover all of this material in a three credit-hour course, you may wish to omit some subjects. You may also wish to supplement the materials in this casebook with additional materials. We encourage you to use this casebook in any way that you like.